If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(5n + 3) + -2(n + -2) = 36 Reorder the terms: -4(3 + 5n) + -2(n + -2) = 36 (3 * -4 + 5n * -4) + -2(n + -2) = 36 (-12 + -20n) + -2(n + -2) = 36 Reorder the terms: -12 + -20n + -2(-2 + n) = 36 -12 + -20n + (-2 * -2 + n * -2) = 36 -12 + -20n + (4 + -2n) = 36 Reorder the terms: -12 + 4 + -20n + -2n = 36 Combine like terms: -12 + 4 = -8 -8 + -20n + -2n = 36 Combine like terms: -20n + -2n = -22n -8 + -22n = 36 Solving -8 + -22n = 36 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -22n = 36 + 8 Combine like terms: -8 + 8 = 0 0 + -22n = 36 + 8 -22n = 36 + 8 Combine like terms: 36 + 8 = 44 -22n = 44 Divide each side by '-22'. n = -2 Simplifying n = -2
| 10(2x+4)=-(8-9x)+3x | | d-1=-16 | | -12=-2n+5n | | -6x+9=27 | | 9(9x+8x)=-10 | | 6v^2-4=1+3v^2 | | 2ci+1=-d+6+-1ci | | 6w(8)=208 | | m-2m=-2 | | 3x-7+7x=-1x+5x | | (a+b)5a+(a+b)3b=0 | | 7x+12=-12 | | 5x+7x=9x-40 | | x-.18x=410 | | r^2=-20-9r | | k+2+5k=8 | | -z=5z | | 5x+2=x+6(x-3) | | -8+(c-2)=-3+2 | | -6(x+1)-11=24+7 | | 9(10x-5)=6 | | 4x-8+17x=16 | | 2a^2-6a=0 | | y^2-2y+11=0 | | 5+2695489649999666887433= | | 3k-15=16 | | .8t+.2(t-.4)=1.75 | | 9-5x=4x+27 | | 2x-10=-32 | | 15=-15-8w | | 64=t+7t | | -2x+8+6x=24 |